Characterization of Pulmonary Rehabilitation Programs in Canada in 2005 - Dina Brooks; Rebecca Sottana; Barbara Bell; Mary Hanna; Lisanne Laframboise; Sugi Selvanayagarajah; Roger Goldstein (Canadian Respiratory Journal)
BACKGROUND: Pulmonary rehabilitation (PR) is recognized as the prevailing standard of care for patients with chronic respiratory conditions. National surveys of PR programs provide important information regarding the structure, content and organization of these programs.